Encyonema hamsherae, a new diatom species from the Northern Rocky Mountains, USA - Winter, Diane; Bahls, Loren (Phytotaxa, 2013)
A new species of Encyonema is described from the benthos of small mountain streams and rivers in western Montana and northern Wyoming. Previously this species had been identified incorrectly as E. hebridicum Grunow ex Cleve and Cymbella affinis Kützing or assigned the provisional name Encyonema sp. 1 MONTANA HAMSHER ANSP. Here we formally recognize this taxon as a new species, Encyonema hamsherae.